2009
DOI: 10.2113/jeeg14.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeophysical Assessment of Wadi El-Sheikh Aquifer, Saint Katherine, South Sinai, Egypt

Abstract: Over the last few years, Saint Katherine, South Sinai has seen large scale development in connection with building new cities, land reclamation, and tourism. The Wadi El-Sheikh aquifer constitutes one of the major freshwater recourses in the Saint Katherine area. In that regard, ten Schlumberger vertical electrical soundings (maximum [Formula: see text]) associated with a number of measured and∕or calculated geoelectric and petrophysical parameters of the aquifer were conducted to delineate and assess the aqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Freely available MATLAB-based software (Sundarajan et al; 2011) was used to process the measured components of the VLF-EM data. The filtered real data anomaly inflections appear as peak positive anomalies and false VLF anomaly inflections as negative anomalies of the profiles (Adiat et al;2009). Subsequently the filtered real in addition to the filtered imaginary data was plotted against distance to generate the VLF-EM profiles.…”
Section: Data Processing and Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Freely available MATLAB-based software (Sundarajan et al; 2011) was used to process the measured components of the VLF-EM data. The filtered real data anomaly inflections appear as peak positive anomalies and false VLF anomaly inflections as negative anomalies of the profiles (Adiat et al;2009). Subsequently the filtered real in addition to the filtered imaginary data was plotted against distance to generate the VLF-EM profiles.…”
Section: Data Processing and Data Interpretationmentioning
confidence: 99%
“…The Very Low Frequency Electromagnetic (VLF-EM) is an effective tool in mapping conductive fault and fracture zones, while resistivity method is used for detecting groundwater presence and differentiating sub surface layers. Electromagnetic and electrical methods have been widely used in groundwater investigations because of good correlation between electrical properties, geological (composition) and fluid content (Olayinka et al;2004, Khali, 2009Jayeoba and Oladunjoye, 2013;Chinyem et al;2014;Taiwo et al;2016). In this present study, Very Low…”
mentioning
confidence: 99%
“…The above-mentioned parameters introduce the concept of anisotropy (λ), where the block of layers as one unit behaves like an anisotropic medium characterized by the longitudinal and transverse resistivities (Maillet 1947;Khalil 2009). The values of electrical anisotropy (λ), as shown in table 2, ranges from 0.5 (VES 17) to 3.0 (VES 11) with an average of 1.21 in the study area and its distribution is shown in figure 3(e).…”
Section: Electrical Anisotropymentioning
confidence: 99%
“…Khalil (2009) observed that when the longitudinal, transverse and mean resistivities differ, then the change in resistivity is dependent on the direction of groundwater flow and the influence of lithological variation. These three types of resistivity values are different in layered anisotropic sediments (Mazac et al 1985;Ayolabi et al 2010).…”
Section: Root Mean Square Resistivitymentioning
confidence: 99%
“…So groundwater mapping is an essential part of the selected site due to the irrigation and agriculture. The latest trends of the aquifer mapping study have been carried out by hydrogeologist and geophysicists (Griffiths and Barker1993;Mondal et al 2008aMondal et al , b, 2009Khalil 2009;Aizebeokhai 2010;Selvam et al 2014). The geophysical study such as electrical resistivity imaging technique is used to estimate the vertical and horizontal changes of subsurface structural changes without any disturbance.…”
Section: Introductionmentioning
confidence: 99%